Enforcing obligations erga omnes in international law - Tams, Christian J (Cambridge University, 2013)
The concept of obligations erga omnes - obligations to the international community as a whole - has fascinated international lawyers for decades. This book shows how this highly controversial concept has become part of modern-day international law, and how it will enhance human rights in the future.